Mukaiyama reagent/NaNO2/wet SiO2 as a mild and heterogeneous reagent system for the N-nitrosation of amines and preparation of azides from hydrazines. Issue 41 (7th October 2015) - Azadi, Roya; Kolivand, Khatereh
Graphical abstract: Abstract: The combination of the Mukaiyama reagent and sodium nitrite in the presence of wet SiO2 was found to be an effective system for the conversion of amines into N -nitrosamines and hydrazines into azides. The heterogeneous reaction proceeded in good to excellent yields and possesses advantages such as the use of non-hazardous reagents, and simple reaction work-up.